The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.bbrc.2017.08.115
|View full text |Cite
|
Sign up to set email alerts
|

Lowering the concentration affects the migration and viability of intracerebroventricular-delivered human mesenchymal stem cells

Abstract: Due to their widely known therapeutic benefits, mesenchymal stem cells have been proposed as a novel treatment option for a wide range of diseases including Alzheimer's disease. To maximize these benefits, critical factors such as delivery route, cell viability, and cell migration must be accounted for. Out of the various delivery routes to the brain, the intracerebroventricular (ICV) route stands out due to the widespread distribution that can occur via cerebrospinal fluid flow. The major objective of this pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…Preconditioning with ethionamide enhanced the migration ability of MSCs, and CXCR4 and CXCL12 were involved in this process ( Figure 4 ). In previous studies, the administration route and dosage were optimized to acquire even distribution of the transplanted MSCs in both canine and mouse models [ 53 , 54 ]. Based on these findings, MSCs were injected into the lateral ventricle of the mouse brain and ETH-MSCs demonstrated a consistently higher migration ability compared to that of naive MSCs in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Preconditioning with ethionamide enhanced the migration ability of MSCs, and CXCR4 and CXCL12 were involved in this process ( Figure 4 ). In previous studies, the administration route and dosage were optimized to acquire even distribution of the transplanted MSCs in both canine and mouse models [ 53 , 54 ]. Based on these findings, MSCs were injected into the lateral ventricle of the mouse brain and ETH-MSCs demonstrated a consistently higher migration ability compared to that of naive MSCs in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have explored how the survival of these preconditioned MSCs are altered following transplantation into the brain. In particular, most human MSCs transplanted into the mouse brain are barely detectable by day 7 post-transplantation [ 39 , 53 , 65 ]. As shown in Figure 5 , the survival of ETH-MSCs was greater than that of naïve MSCs in the mouse brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, a previous study from our group showed that the injection concentration can affect the distribution of MSCs after injecting stem cells via the intracerebroventricular route. At higher concentrations, MSCs tended to aggregate, forming clumps, whereas at lower concentrations, MSCs were easily washed out via CSF flow [14]. Second, the cell dose may affect the migration of MSCs towards the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Optimizing the administration dose and improving the therapeutic efficacy of MSCs must be considered in order to maximize clinical efficacy [14]. Choosing the optimal delivery route is especially important for CNS diseases [15].…”
Section: Introductionmentioning
confidence: 99%